A bibliometric analysis of acupuncture for Parkinson's disease non-motor symptoms from 2003 to 2023 - Mina Wang; Chunying Ma; Anming Liu; Hongli Xiao; Yashuo Ren; Zhuohao Li; Zixi Wang; Qiuyu Xia; Pu Dou; Bin Li; Peng Chen (Elsevier, 2024)
Background: Parkinson's disease non-motor symptoms (PD-NMS) significantly affect patients' quality of life. Acupuncture has emerged as a potential complementary therapy for PD-NMS. This study aims to investigate general research status, hotspots and trends of acupuncture as a treatment for PD-NMS. Methods: Literature on Web of Science Core Collection (WoSCC) from 2003 to 2023 was retrieved, and bibliometric analysis was conducted using VOSviewer and CiteSpace software. Results: 159 publications by 894 authors from 37 countries, 300 institutions, and 96 journals were retrieved and analyzed. The number of publications in this field is generally on the rise yearly. China was the leading contributor with 57 publications, and the United States followed with 36 publications and had the highest total citation count of 1562. Guangzhou University of Chinese Medicine ranked the highest with a total of 12 publications, while Harvard University had the highest average citation rate of 70 citations per publication. Evidence-Based Complementary and Alternative Medicine was the most prolific journal with 11 articles that had accumulated 122 citations. Park Hi-Joon was the leading contributor with seven articles and 314 citations. The keyword analysis highlighted emerging areas of interest like "deep brain stimulation" and "alpha-synuclein". Conclusion: Different countries, institutions, and authors should enhance cooperations, and the underlying mechanisms of acupuncture for PD-NMS should be demonstrated. This study will be helpful for better understanding the current knowledge and gaps in the areas of acupuncture as a treatment of PD-NMS.